The degree of agreement between score-based decision and clinician's discretion regarding the need for tracheotomy in oral cancer surgery: A retrospective analysis. Issue 30 (30th July 2021) - Abe, Atsushi; Ito, Yu; Hayashi, Hiroki; Furuta, Hiroshi; Ishihama, Takanori; Adachi, Moriyasu
Abstract : Abstract: In oral cancer surgery, the decision to perform a tracheotomy is often determined by the surgeon. In this study, we investigated the competency of clinical scoring systems in identifying patients who require tracheotomy and examined the degree of agreement between the surgeon's decision and the indications of various scoring systems. We identified 110 patients who were surgically treated for oral cancer. Of these, 67 patients (44 men and 23 women) who underwent resection and reconstruction were retrospectively analyzed. To derive the score, we evaluated the endpoint of the airway management score using clinical records and images. We divided the patients into two groups based on the Cameron and Gupta scores (tracheotomy and no-tracheotomy groups) and evaluated the degree of agreement with the surgeon's decision by calculating the κ coefficient. The κ coefficients of the Gupta and Cameron scores were 0.61 (95% confidence interval [CI]: 0.40–0.82) and 0.60 (95% CI: 0.38–0.82), respectively. The clinical evaluation of the κ coefficient indicated that the Cameron and Gupta scores agreed fairly with the surgeon's decision. In this study, the Cameron and Gupta scores fairly agreed with the decision of experienced surgeons and were confirmed as acceptable guides for making clinical judgments.